2006
DOI: 10.1504/ijgei.2006.008383
|View full text |Cite
|
Sign up to set email alerts
|

Carbon dioxide capture: an assessment of plausible ranges

Abstract: The projections of energy related carbon dioxide (CO 2) emissions in the Special Report on Emission Scenarios (SRES) of the Intergovernmental Panel on Climate Change (IPCC) serve as point of departure for an assessment of plausible ranges of CO 2 emissions that could be avoided through CO 2 capture and storage measures. Scenario and time dependent, sector and fuel specific capture factors are developed for eleven world regions to estimate the proportion of CO 2 resulting from fossil fuel and biomass combustion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Figure shows the context for the CCS deployment assumed in this study. On the basis of the IPCC SRES A2 scenario, Toth and Rogner estimated that the technical potential of CCS in the United States would be 3.6 Gt CO 2 /year in the power sector in 2050 under the A2-IMAGE scenario and 1.8 Gt CO 2 under the A2-AIM scenario. Riahi et al reported that OECD90, defined as all members of OECD in 1990, would capture 3.5–5.9 Gt CO 2 in 2050.…”
Section: Ammonia Emissions From Amine Scrubbingmentioning
confidence: 99%
“…Figure shows the context for the CCS deployment assumed in this study. On the basis of the IPCC SRES A2 scenario, Toth and Rogner estimated that the technical potential of CCS in the United States would be 3.6 Gt CO 2 /year in the power sector in 2050 under the A2-IMAGE scenario and 1.8 Gt CO 2 under the A2-AIM scenario. Riahi et al reported that OECD90, defined as all members of OECD in 1990, would capture 3.5–5.9 Gt CO 2 in 2050.…”
Section: Ammonia Emissions From Amine Scrubbingmentioning
confidence: 99%